Economic feasibility, general economic impact and implications of a free trade agreement between the European Union and Armenia - David Dyker; Michael Emerson; Michael Gasiorek; Peter Holmes; Malgorzata Jakubiak; Andre Jungmittag; Vicki Korchagin; Alina Kudina; Evgeny Polyakov; Andrei Roudoi; Svetlana Taran; Gevorg Torosyan (Center for Social and Economic Research (CASE), 2008)
Our mandate was to consider the economic feasibility and possible impact of a free trade agreement between the European Union and Armenia. The study has been conducted by a group of researchers from Poland, Ukraine, UK, US and Armenia. All have worked on this project in an independent capacity. The European Commission has also commissioned a similar study for Georgia. Even though the methodology of the two reports is the same, the two studies are independent and the economic feasibility and impact of a free trade agreement with each country is assessed on its own merits. [...]
Keywords: F15; F12; O13; P48; G21; 330; European Neighborhood Policy; free trade agreement; institutional harmonization; EU; Armenia; Freihandelszone; Regionale Wirtschaftsintegration; EU-Nachbarstaaten; Makroökonomischer Einfluss; EU-Staaten; Armenien